2017
DOI: 10.1039/c7cp03843g
|View full text |Cite
|
Sign up to set email alerts
|

Ergothioneine and related histidine derivatives in the gas phase: tautomer structures determined by IRMPD spectroscopy and theory

Abstract: l-Ergothioneine (ET) is a sulfur-containing derivative of the amino acid histidine that offers unique antioxidant properties. The enzyme independent redox-chemistry of ET relies on the availability of the thiol tautomer to allow oxidative formation of disulfide bridges, i.e., the tautomeric equilibrium. To study the intrinsic properties of ET the tautomeric equilibrium is studied in the gas-phase by infrared multiphoton dissociation (IRMPD) spectroscopy. The IR ion spectra of isolated molecular ions of ET and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 52 publications
1
12
0
Order By: Relevance
“…Similar cases of nonthermal behavior have previously been reported [24–26] . A prominent example is ergothionein, a 2‐mercaptohistidine trimethyl betaine, which preferably adopts a thione tautomeric ion structure in MeOH solution, which is also carried over to and identified in the gas phase [27] …”
Section: Resultssupporting
confidence: 73%
“…Similar cases of nonthermal behavior have previously been reported [24–26] . A prominent example is ergothionein, a 2‐mercaptohistidine trimethyl betaine, which preferably adopts a thione tautomeric ion structure in MeOH solution, which is also carried over to and identified in the gas phase [27] …”
Section: Resultssupporting
confidence: 73%
“…a thione ion structure in the gas phase. 29 To probe this aspect, a number of geometry optimizations were performed using a simulated MeOH solvent environment. In particular, we investigated isomers 4B, 4C, 4E, and 4F as the most probable isomers in the gas phase, based on the experimental IRMPD data.…”
Section: Structure Elucidation Of the Charge-tagged Phenyl Pyruvic Acmentioning
confidence: 99%
“…Frequencies were scaled by 0.97 in the wavenumber range of 600-1900 cm Ð1 and in the wavenumber range of 3400-3800 cm Ð1 with a factor of 0.95 to account for anharmonicity and convoluted with a Gaussian line shape function with a FWHM of 12 cm Ð1 to facilitate comparison with experiment. 29,31,43 Energy differences quoted throughout the paper are based on Gibbs free energies (298 K, 1 bar). All transition states were checked to connect the correct energy minima through an intrinsic reaction coordinate calculation.…”
Section: Computationsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14] This can be an analytical problem when protomers dissociate to different product ions under activation, a phenomenon that can confound assignment by comparison to reference spectra. Differences in the photodissociation of protomers have been used to assign protomer populations, [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] although it is difficult to predict how the electronic spectroscopy and photodissociation will be affected by differences in protonation site. Hence, analysing the photodissociation of selected protomers, can provide insights into the effects of protonation on excited quantum states of ions while progressing towards the use of photo-dissociation as a method to disambiguate and assign protomers.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have taken advantage of the differences in photoactivity of protomers and made assignments by comparing theoretical transition simulations to experimental results obtained by UV photodissociation action spectroscopy, [13][14][15][16][17][24][25] or IRMPD. [10][11][18][19][20][21][22][23] Dessent and co-workers have demonstrated the potential for moderate-resolution UV action spectra, coupled with TD-DFT analysis, to detect and assign protomers of nicotinamide and paminobenzoicacid. 12,26 These studies reported different action spectrum profiles of Oprotonated or N-protonated isomers.…”
Section: Introductionmentioning
confidence: 99%